Postoperative Pain After Mohs Micrographic Surgery is Well Tolerated Regardless of Psychological and Pain-Related Comorbidities. Issue 4 (April 2021) - Brahe, Catherine A.; Hardy, Curtis Lamar; Miladi, Anis
Abstract : BACKGROUND: Preoperative patient screening has been evaluated in many surgical specialties as a way to improve the overall patient experience. Current data are limited regarding patient screening for dermatologic procedures. The goal of preoperative screening is to identify patients at risk for poor outcomes and tailor the treatment plan to ensure a greater overall patient experience. OBJECTIVE: To investigate the association between psychological comorbidities and acute postoperative pain in patients treated with Mohs micrographic surgery (MMS). MATERIALS AND METHODS: Subjects were recruited from a single center, single provider, uniformed service MMS practice, and asked to complete preoperative and postoperative questionnaires for scheduled MMS. Outcome variables included anticipated pain, actual pain after MMS, duration of pain, and medications used for pain. RESULTS: Mohs micrographic surgery was well tolerated. There were no significant differences in anticipated or reported pain, or in medication use between cohorts. Significant differences in pain were noted with closure technique with complex surgical repairs generating the greatest pain across groups. CONCLUSION: Mohs micrographic surgery is well tolerated by patients, both with and without psychological comorbidities. Our results show no statistically significant differences, suggesting a limited role for preoperative screening as a tool to guide pain management after MMS.